A Modified Simplified Reference Tissue Model for the Quantification of Dopamine D Receptors with [F]Fallypride Images - Stergios Tsartsalis; Marcelle Moulin-Sallanon; Noé Dumas; Benjamin B. Tournier; Nathalie Ginovart; Philippe Millet (Molecular Imaging)
Defluorination of [ 18 F]fallypride and accumulation of 18 F in skull and glands leads to the contamination of brain structures with spillover activity due to partial volume effects, leading to considerable errors in binding potential estimations. Here we propose a modification of the simplified reference tissue model (SRTM) to take into account the contribution of skull activity to the radioactivity kinetic pattern in cerebellum and target regions. It consists of the introduction of an additional parameter for each volume of interest (s T ) and one for the cerebellum (s R ), corresponding to the fraction of skull activity contaminating these structures. Using five rat positron emission tomography experiments, we applied the modified SRTM (SRTMc), which resulted in excellent fits. As a relative means of comparison of results, we applied factor analysis (FA) to decompose dynamic data into images corresponding to brain and skull activity. With the skull factor images, we estimated the “true” s T and s R values, ultimately permitting us to fix the s R value. Parameters obtained with the SRTMc were closely correlated with values obtained from FA-corrected data. In conclusion, we propose an efficient method for reliable quantification of dopamine D 2/3 receptors with single-injection [ 18 F]fallypride scans that is potentially applicable to human studies where 18 F skull accumulation compromises binding parameter estimation.